Impact of suspected food allergy on emotional distress and family life of parents prior to allergy diagnosis. Issue 8 (13th December 2013) - Knibb, Rebecca C.; Semper, Heather
Abstract Background Food allergy is associated with psychological distress in both child and parent. It is unknown whether parental distress is present prior to clinical diagnosis or whether experiences at clinic can reduce any distress present. This study aimed to assess anxiety and depression in parents and the impact of suspected food allergy on the lives of families before and after a visit to an allergy clinic. Methods One hundred and twenty‐four parents visiting an allergy clinic for the first time to have their child assessed for food allergy completed a study‐specific questionnaire and the Hospital Anxiety and Depression Scale; 50 parents completed these 4–6 wk later in their own home. Results Most parents (86.4%) reported suspected food allergy had an impact on their family life prior to clinic attendance; 76% had made changes to their child's diet. 32.5% of parents had mild‐to‐severe anxiety before their clinic visit; 17.5% had mild‐to‐moderate depression. Post‐clinic, 40% had mild‐to‐severe anxiety; 13.1% had mild‐to‐moderate depression. There were no significant differences in anxiety (p = 0.34) or depression scores (p = 0.09) before and after the clinic visit. Conclusions Anxiety and depression is present in a small proportion of parents prior to diagnosis of food allergy in their child and this does not reduce in the short term after the clinic visit. Identification of parents at risk of suffering from distress is needed and ways in which we communicate allergy information before and at clinic should be investigated to see if we can reduce distress.